Relative Motion Flexion Splinting for Flexor Tendon Lacerations: Proof of Concept. (March 2019) - Chung, Bryan; Chiu, David T. W.; Thanik, Vishal
Background: The principle of relative motion has allowed patients to regain a higher degree of hand function, while protecting extensor tendon repairs. The purpose of this study was to determine whether the principle of relative motion could be a viable method to protect a flexor tendon repair.Methods: Four fresh-frozen cadaver arms were each mounted on a testing apparatus (wrist in 30° of extension, metacarpophalangeal [MCP] joints blocked to 70°-80°). A minimum of 11 N was used to cyclically load the flexor digitorum profundus and extensor digitorum communis tendons to maximum allowable flexion and extension for 25 cycles. Measurements of elongation of the tendons were obtained through the use of differential variable reluctance transducers. Testing was performed in both intact and repaired (single 6-0 nylon suture) middle finger tendons (zone 3) with and without a relative motion flexion splint (RMFS), which placed the affected finger in 15° to 25° of relative flexion at the MCP joint.Results: In all 4 hands, elongation was restricted to less than 1.3 mm in repaired tendon in the RMFS compared with elongation >2 mm in the nonsplinted condition. Average elongation was 0.86 mm (SD = 0.45). Visual examination of the tendons demonstrated no gapping with the use of the RMFS in any of the hands. All repairs had suture breakage and repair rupture without the RMFS.Conclusions: This study demonstrates that the RMFS decreases elongation and eliminates tendon-repair gapping after flexion/extension cycling in a cadaver model. It provides proof of concept that the RMFS may be a viable protective mechanism for flexor tendon repairs in zone 3.